PEMANFAATAN TEMPE DENGAN JAMUR TIRAM (Pleurotus ostreatus) DALAM PEMBUATAN NUGGET - Bondan Sumantri; Akhyar Ali; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to obtain the best nugget formulation of utilization tempeh and oyster mushrooms both in terms of organoleptic and nutritional substances nuggets. This research used Complete Randomized Design (CRD) with four treatments and four replications. The treatments were TJ1 (95% Tempe, 5% oyster mushroom), TJ2 (90% Tempe, 10% oyster mushroom), TJ3 (85% Tempe, 15% oyster mushroom), TJ4 (80% Tempe, 20% oyster mushroom). The data obtained were analyzed using analysis of variance followed by Duncan's New Multiple Range Test (DNMRT) at 5% level. Results showed that the ratio of tempeh and oyster mushroom in each treatment significantly affected the moisture content, ash content, fiber content, protein content and flavor, but did not significantly affect the elasticity, adhesiveness, aroma, colour and overall assessment. The best treatment in this study is TJ1 (95% Tempe, 5% oyster mushroom) with a moisture content 46,62%, protein content 16,29%, ash content 0,47% and fiber content 3,47%. Keywords: Nugget, Tempeh, Oyster mushroom